2020
DOI: 10.3390/plants9010111
|View full text |Cite
|
Sign up to set email alerts
|

Silicification of Root Tissues

Abstract: Silicon (Si) is not considered an essential element, however, its tissue concentration can exceed that of many essential elements in several evolutionary distant plant species. Roots take up Si using Si transporters and then translocate it to aboveground organs. In some plant species, root tissues are also places where a high accumulation of Si can be found. Three basic modes of Si deposition in roots have been identified so far: (1) impregnation of endodermal cell walls (e.g., in cereals, such as Triticum (wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 159 publications
(261 reference statements)
2
21
0
Order By: Relevance
“…The endodermis plays a crucial role in reducing metal transport toward the central cylinder, and in the present study, Si deposition was increased in the endodermis during Cd and Zn stress in rice and maize, which potentially increases the physical defense exhibited by the endodermis. Si is a normal component of the endodermis of cereals, and the mode of Si deposition may be impregnation or Si‐aggregate formation (Lux et al, 2020). Similar to our results, when maize plants were grown on Cd‐ and Zn‐enriched soil, the deposition of silica bodies was prominently observed in the endodermis of roots (da Cunha & do Nascimento, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The endodermis plays a crucial role in reducing metal transport toward the central cylinder, and in the present study, Si deposition was increased in the endodermis during Cd and Zn stress in rice and maize, which potentially increases the physical defense exhibited by the endodermis. Si is a normal component of the endodermis of cereals, and the mode of Si deposition may be impregnation or Si‐aggregate formation (Lux et al, 2020). Similar to our results, when maize plants were grown on Cd‐ and Zn‐enriched soil, the deposition of silica bodies was prominently observed in the endodermis of roots (da Cunha & do Nascimento, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Plant-available Si: In addition to the different Si pools measured through the sequential extraction, we also estimate the soil Si fraction readily available to plants. Multiple methods exist to measure this soluble Si pool (Liang et al 2015;Sauer et al 2006). One way is to take the sum of Si M and Si Ads from the sequential extraction (Si M?Ads ), as Si M and Si Ads are both readily soluble and available to plants (Haynes 2014;Sauer et al 2006).…”
Section: Si Pools In Soilsmentioning
confidence: 99%
“…Si enhances plant resistance in a large variety of circumstances, including for example nutrient depletion, drought stress, pathogens and pest attacks. There is evidence for multiple combined beneficial effects of Si rather than one single mechanism (Guntzer et al 2012a;Liang et al 2015;Rizwan et al 2015). The functioning of these effects is, however, far from being fully understood and is still subject to debate (Coskun et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing numbers of reports have adequately documented the beneficial effects of silicon in enhancing the disease resistance of plants to several pathogens, but the exact mechanisms underlying this phenomenon remain controversial [4,9,12,13]. Some studies suggest that the enhanced resistance to disease in Si-accumulating plants has been linked with mechanical barriers, due to accumulation and polymerization of Si in different organs and limited pathogen penetration and invasion [8,9,[12][13][14][15]. Studies also showed that Si may play a more active role in enhancing plant resistance to pathogen infection by activating the defence responses in the host, including the production of defence proteins, antimicrobial compounds [16][17][18].…”
Section: Introductionmentioning
confidence: 99%